High strength extrafine pMDI beclometasone/formoterol (200/6 μg) is effective in asthma patients not adequately controlled on medium-high dose of inhaled corticosteroids. Issue 1 (December 2016) - Paggiaro, Pierluigi; Corradi, Massimo; Latorre, Manuela; Raptis, Helene; Muraro, Annamaria; Gessner, Christian; Siergiejko, Zenon; Scuri, Mario; Petruzzelli, Stefano
Abstract Background A high strength of beclomethasone/formoterol fumarate (BDP/FF) ina pressurised metered dose inhaler (pMDI), which contains extrafine BDP (200 μg/actuation) and FF (6 μg/actuation) has been developed to treat those asthmatics who are not adequately controlled on previous treatments. Methods A 12-week, randomized, double-blind, parallel group study was performed to compare the efficacy and safety of pMDI BDP/FF 200/6 (two actuations bid) with BDP 100 μg (four actuation bid) in a population of 376 randomized adult asthmatics not adequately controlled with high dose of inhaled corticosteroids (ICS) or medium dose of ICS plus long acting β2 agonists (LABA). Results The primary endpoint [change from baseline over the entire treatment period in average pre-dose morning peak expiratory flow (PEF)] demonstrated the superiority of BDP/FF over BDP monotherapy, with an adjusted mean difference of 19 L/min, which is above the minimal important clinical difference reported for this parameter. Overall, BDP/FF and BDP showed a similar improvement of symptom-based parameters and of the use of rescue medication after 3-month treatment. The safety profile of the two drugs was comparable, although BDP monotherapy, but not BDP/FF, slightly reduced the levels of serum cortisol. Conclusions The study proved that pMDI BDP/FF 200/6 μg was superior to BDP alone in improving lung function with comparable safety profiles. Therefore it may be considered as an effective treatment for adults with asthma not adequately controlled with high dose of ICS monotherapy or medium dose of ICS/LABA combinations. Trial registration ClinicalTrials.gov:NCT01577082, date 06/04/2012.